Lessons from the graduates of one-year theological programs in the Australian College of Theology - Hussey, Ian; Bain, Andrew M. 1970- (2020)
The uptake in one-year theological programs by students in the Australian College of Theology (ACT) has heightened interest in the question of whether these short qualifications meet the expectations of students and equip them for their ministry, whether that be in their local church, parachurch organizations or other vocations. This article reports on a survey of graduated students from one-year ACT programs. The research explored how well the qualification met the expectations of students. The survey also asked students to indicate how well the short course contributed to the growth of the ACT graduate attributes within themselves. The research concludes that the one-year qualifications are “fit for purpose” especially in deepening the graduate's relationship with God and knowledge of the Bible. However, the research also indicates that ACT colleges need to consider ways they can enhance the short courses in order to make them more relational and equip students for the practical application of the concepts they have learnt in their course.
Keywords: graduate attributes; one-year programs; one-year qualifications; student evaluation